PENERAPAN PBL UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS X TKR 1 SMK MUHAMMADIYAH 1 PEKANBARU - Tia Andesma; Rini Dian Anggraini (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2019)
This study aimed to improve the learning process and the student’s mathematical problem solving skill by applying Problem Based Learning (PBL)l. This type of study is classroom action research with two cycles. This study was conducted in collaboration between researcher and teacher of mathematics. Subjects were students of class X TKR 1 SMK Muhammadiyah 1 Pekanbaru. The study was conducted in the second semester of academic year 2018/2019. The research instrument consists of mathematical learning instruments and instruments to collect data. Mathematical learning instruments are syllabus, lesson plans, and students’ worksheets. Data collection instruments are observation sheets and mathematical problem solving tests. Data analysis techniques are analysis descriptive narrative of qualitative data and descriptive statistical analysis of quantitative data. The result of this study showed that the implementation of PBL improved the learning process and the student’s mathematical problem solving skill. The average of student’s mathematical problem solving skill in firts cycle which is 72,09 had improved to 85,67 in second cycle. The improvement also found in the indicator average value in identifying the problem, devising a plan to solve the problem, carrying out the plan to solve the problem, and interpreting the solution. This study concludes that the implementation of PBL improved the student’s mathematical problem solving skill at class X TKR 1 SMK Muhammadiyah 1 Pekanbaru. PBL can be used as an alternative to learning, because through this learning can improve mathematical problem solving skill of the students.